PENERAPAN CCTV (CLOSET CIRCUIT TELEVISION) DALAM UPAYA MENGURANGI PELANGGARAN LALU LINTAS DI KOTA PEKANBARU - Wahyudi, Mahesa; Askarial (Sisi Lain Realita, 2023)
Traffic violations are one of the problems that often cause problems on the highway. In the context of traffic guidance, the use of technology is often used, one of which is CCTV (Closed Circuit Television) which is used to assist the police in carrying out traffic violation efforts. However, the phenomenon that occurs in the field is found that the police's efforts to utilize CCTV as an effort to reduce the number of traffic violations have not run optimally. In this study the problem will be reviewed using the theory of crime prevention efforts. This research was carried out using a qualitative method with a descriptive type of research with the main data of the research obtained through interviews with Etle CCTV operators, Pekanbaru Police Legal Aid, communities around EtleCCTV in Pekanbaru City and traffic light violators recorded by Etle CCTV. Based on the results of the interviews that have been conducted, it can be concluded that the application of Etle CCTV can be said to be quite effective because the ETLE system prevents officers and offenders from meeting face to face, resulting in the phenomenon of extortion during sentence enforcement. However, the application of this CCTV system is not entirely effective, because there are still many people who commit violations and only follow traffic rules when police officers are on duty. There are several locations for ETLE CCTV camera installation points in Pekanbaru City, namely on Jalan Jenderal Sudirman in front of the Riau Police Bhayangkara Hospital, Simpang Raya Jalan Harapan Raya - Jenderal Sudirman (below the flyover), Jalan HR Subrantas-Jalan SM Amin and Jalan Nangka Simpang Mall SKA. The sanctions given to traffic violators who are detected by CCTV are explained in Law no. 29 of 2009 regarding road traffic and transportation